Sociocultural Issues Represented in Native Son Novel by Richard Wright - Kathrin Meylida Annur; Fatchul Mu’in; Nasrullah Nasrullah; Rina Listia (IDEAS: Journal on English Language Teaching and Learning, Linguistics and Literature, 2023)
A novel is one of the types of literature that retells real-world events in a fictional way without taking away their social or cultural parts. This research was conducted to analyze Native Son, a novel about Bigger Thomas's life as a black person in America in the 1930s. The issues explored in this novel include racial prejudice, racial discrimination, and racial segregation. This study used an interdisciplinary approach, a mimetic approach, and a document study. The data are collected by reading the novel, taking the contents representing the issues, and then presenting and explaining what the data mean. The study results show that Native Son portrays some of the sociocultural issues that often occur in society. This study is expected to provide readers with information on how to analyze a literary work, specifically a novel, and to gain a greater understanding of sociocultural issues in society so that it can be used as a reflection of life.